2014
DOI: 10.1124/mol.114.094508
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: STAT3 Regulates Steady-State Expression of Synaptopodin in Cultured Mouse Podocytes

Abstract: The transcription factor signal transducer and activator of transcription-3 (STAT3) is activated by proinflammatory cytokines and circulating factors in many cell types. Synaptopodin (Synpo) is a cytoskeleton regulatory protein expressed in podocyte foot processes that regulates the dynamics of actin filaments and the stability of small GTPases. Here we show that inhibition of STAT3 signaling using the small-molecule inhibitor benzo [b]thiophene, 6-nitro-,1,1-dioxide (Stattic), or by STAT3 knockdown by small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Podocytes play an essential role in the maintenance of the integrity of the glomerular filtration membrane, and injury to this membrane occurs in many glomerular diseases (30). Increasing evidence indicates that intracellular signaling pathways are involved in changes in the biological function of podocytes under different stimuli (31,32). Our results indicated that PKA signaling might increase mitochondrial oxidative phosphorylation and reduce ROS generation, thus preventing podocyte injury.…”
Section: Discussionmentioning
confidence: 56%
“…Podocytes play an essential role in the maintenance of the integrity of the glomerular filtration membrane, and injury to this membrane occurs in many glomerular diseases (30). Increasing evidence indicates that intracellular signaling pathways are involved in changes in the biological function of podocytes under different stimuli (31,32). Our results indicated that PKA signaling might increase mitochondrial oxidative phosphorylation and reduce ROS generation, thus preventing podocyte injury.…”
Section: Discussionmentioning
confidence: 56%
“…The proteinuria we observed in the SS rats fed a HS diet was expected to be attenuated by E‐64 treatment. In cultured podocytes, E‐64 was recently reported to block an Ang II‐induced, STAT3 mediated loss of the cytoskeleton regulatory protein synaptopodin (Abkhezr and Dryer ). The absence of attenuated albuminuria suggests that cysteine Caths are not involved in the development of SS hypertension‐associated proteinuria.…”
Section: Discussionmentioning
confidence: 99%